Bophelo dominant discourses: internalised understandings: an analysis of the dominant discourses of health in Lesotho and how they affect healthcare providers' health perceptions - Graham, Lauren (My University, 2010)
ABSTRACT This dissertation is a study of how Basotho healthcare providers understand health. It leads directly to a discussion of the health discourses evident in Lesotho and the way in which they impact on the perceptions of health that healthcare providers hold. The approach used was to conduct a case study of nurses, nurse assistants and technicians at Scott Hospital in Morija, Lesotho. The findings revealed that the perceptions of health that these healthcare providers hold are profoundly impacted upon by four discourses that are evident in Lesotho, these being the biomedical discourse, the Public Health discourse, the Christian discourse and the traditional discourse of health. These discourses are evident in Lesotho due to a complex interplay of history, economy, politics, development and culture amongst other factors. They play themselves out at various levels – national, local and individual – and represent the power dynamics that are at play when it comes to health in Lesotho. What is key is that each discourse, regardless of official policy, plays an integral role in the perceptions of health that the healthcare providers hold. Four elements are discussed in this dissertation. As will be shown, health, development, religion and tradition have a complex history in Lesotho that has led to the current health picture in Lesotho. As such, this dissertation, whilst being broadly a development piece of work, focuses more acutely on the interplay between health, religion and tradition, and through doing this, makes comment about development more generally.